The Role of Scripture in Theology Is Africa Getting it Right? - Odia, Cyril Aigbadon (2019)
Teaching Christian religious studies in Nigeria, like in many other Christian African countries, is based on the use of Scripture. Such instruction is a continuation of the basic faith formation young people have received from their parents, church, and local community. Effective religious education cannot be restricted only to the classroom but must also include social acts of kindness and community building. African theology in recent years has grown with the rise of African Independent Churches and biblical studies. Scriptural studies in the Nigerian secondary school curriculum help construct the basic platform for sustaining a Scripture-based African theology.
Keywords: African biblical theology; African secondary school religious studies; Christian religious studies in Nigeria; Scripture and theology in Africa; "African time" theology; contextual biblical theology in Nigeria